inggris: inggris - Galang Syafta; Rio Fahni; Aprilia Fitri Ningsih (Faculty of Law, Universitas Lampung, 2022)
Given the lack of a specific institution in Indonesia that oversees the protection of personal data, the importance of protecting personal data is frequently debated. Along with technological developments that continue to occur, it will be directly proportional to the legal risks caused. Hence, these developments need to be balanced with existing legal rules to minimize the occurrence of criminal cases, one of which is the misuse of technology today, which is related to property rights to personal data, especially personal data on social media. This paper uses a normative research method that aims to determine the essence of the formation of legal products and independent authority institutions in Indonesia in maximizing protection and law enforcement against misuse of personal data. Based on the results of the study, it is known that the urgency of establishing this independent authority greatly influences the protection of the misuse of personal data, especially personal data on social media.